Intraoperative Decision-Making and Technical Aspects of Parathyroidectomy in Young Patients With MEN1 Related Hyperparathyroidism - Nobecourt, Priscilla F.; Zagzag, Jonathan; Asare, Elliot A.; Perrier, Nancy D. (Frontiers in Endocrinology, 2018)
One in 5,000 to 1 in 50,000 births have multiple endocrine neoplasia type 1 (MEN1). MEN1 is a hereditary syndrome clinically defined by the presence of two of the following endocrine tumors in the same patient: parathyroid adenomas, entero-pancreatic endocrine tumors and pituitary tumors. Most commonly, patients with MEN1 manifest primarily with signs and symptoms linked to primary hyperparathyroidism. By age 50, it is estimated that 100% of patients with MEN1 will have been diagnosed with primary hyperparathyroidism. These patients will need to undergo resection of their hyperfunctioning glands, however there is no clear consensus on which procedure to perform and when to perform it in these patients. In this original study we describe and explain the rational of our peri-operative approach and management at MD Anderson Cancer Center of MEN1 patients with hyperparathyroidism. This protocol includes preoperative evaluation, intraoperative decision-making and detailed surgical technique adopted for these patients' care. Additionally we review follow-up and disease management in instances of recurrent primary hyperparathyroidism in patients with MEN1 syndrome.